1993
DOI: 10.1056/nejm199312233292604
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations of AIDS in the Era of Pneumocystis Prophylaxis

Abstract: M. avium complex disease, esophageal candidiasis, wasting syndrome, and cytomegalovirus disease are more common in HIV-infected patients who have received prophylaxis against P. carinii than in those who have not. Prophylaxis may delay the first AIDS illness for 6 to 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
129
0
5

Year Published

1994
1994
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(135 citation statements)
references
References 13 publications
1
129
0
5
Order By: Relevance
“…Such considerations are difficult to quantify but they underscore that the increased risk ofwasting should be of concern. Wasting is a relatively frequent condition in the later stages of HIV infection in industrialized countries (HOOVER et al, 1993) and 'slim disease' is one of the most important AIDS-defining events in many African and other lessdeveloped countries (GRANT et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Such considerations are difficult to quantify but they underscore that the increased risk ofwasting should be of concern. Wasting is a relatively frequent condition in the later stages of HIV infection in industrialized countries (HOOVER et al, 1993) and 'slim disease' is one of the most important AIDS-defining events in many African and other lessdeveloped countries (GRANT et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…As many as 45% of individuals infected with the human immunodeficiency virus (HIV) will develop disease due to cytomegalovirus (CMV) by the end of their lives (8). Two antiviral agents, ganciclovir and foscarnet, are available to treat CMV disease.…”
mentioning
confidence: 99%
“…59 In fact, recent studies have shown an increasing incidence of CMV disease paralleling the widespread use of prophylaxis for Pneumocystis carinii pneumonia. 5,6 CMV disease typically occurs when immunode®ciency is severe (CD4 lymphocyte count < 100/mm 3 ); in these patients, the incidence of disease may approach 21% at 2 years. 60 Although the retina is the most common target for CMV, gastrointestinal involvement remains important because of its frequency and morbidity.…”
Section: Cytomegalovirusmentioning
confidence: 99%